2022
DOI: 10.1371/journal.pone.0270737
|View full text |Cite
|
Sign up to set email alerts
|

Market orientation and technological orientation in business services: The moderating role of organizational culture and human resources on performance

Abstract: Contemporary conditions of the functioning of enterprises mean that they are increasingly looking for opportunities to improve organizational performance in strategic management. Scientists are looking for optimal solutions, an appropriate combination of assets and resources, so the debate in the field of strategic orientations is still valid and gaining in importance. Several studies have explored the construct of market orientation, but few include technological orientation with the moderating effects of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…As the first objective of this study is to identify the impact of independent variablese-marketing orientation (EMO), sustainability orientation (SO), and technology orientation (TO)-on the dependent variable online SME business performance (OBP), we believe that PLS-SEM is appropriate for analyzing the construct model. Therefore, previous marketing studies with similar latent variables were reviewed to analyze the data using PLS-SEM [42][43][44][45][46][68][69][70][91][92][93][94][95]. Multi-group analysis (PLS-MGA) was deemed suitable for examining significant differences between e-commerce intensity groups in the constructions EMO → OBP, SO → OBP, and TO → OBP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the first objective of this study is to identify the impact of independent variablese-marketing orientation (EMO), sustainability orientation (SO), and technology orientation (TO)-on the dependent variable online SME business performance (OBP), we believe that PLS-SEM is appropriate for analyzing the construct model. Therefore, previous marketing studies with similar latent variables were reviewed to analyze the data using PLS-SEM [42][43][44][45][46][68][69][70][91][92][93][94][95]. Multi-group analysis (PLS-MGA) was deemed suitable for examining significant differences between e-commerce intensity groups in the constructions EMO → OBP, SO → OBP, and TO → OBP.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [92], conducting a quantitative study among Polish providers of technological services, found that organizational culture and human resources strengthen the relationship between TO and organizational performance, while weak human resource management diminishes its effect. Ref.…”
Section: Technological Orientation (To)mentioning
confidence: 99%
See 1 more Smart Citation
“…Its relevance has been enhanced by the turbulent environment of today, in which change is occurring at an ever faster pace and the complexity of processes is increasing (Vasconcelos & Ramirez, 2011). Most industries today are experiencing turbulence in economic processes, which makes it even more difficult to choose the right strategic actions (Borodako et al, 2022). Organisations are constantly facing new challenges and it is becoming important for everyone to know how to deal with increasingly complex tasks and challenges as efficiently as possible.…”
Section: Introductionmentioning
confidence: 99%
“…technology necessitates the resolution of novel concepts, innovative techniques, and proactive actions highly influenced by organizational culture(Borodako et al, 2022). Hence, the following statement is reached: H1: Technological capacity positively affects organizational culture According toTsai & Hsieh (2009), an increase in a firm's technological capacity enables it to combine and integrate exploration (external technological knowledge) with exploitation (current expertise) to increase sales of new goods.…”
mentioning
confidence: 99%